Những câu hỏi liên quan
forever love you
Xem chi tiết
Vu Khanh Linh
Xem chi tiết
Chu Khánh Minh Châu
Xem chi tiết
Nguyễn thành Đạt
21 tháng 9 2023 lúc 21:35

Ta có : \(k\left(k+1\right)\left(k+2\right)-\left(k-1\right)k\left(k+1\right)\)

\(=\left(k^2+k\right)\left(k+2\right)-\left(k^2-k\right)\left(k+1\right)\)

\(=k^3+2k^2+k^2+2k-k^3+k\)

\(=3k^2+3k\)

\(=3k\left(k+1\right)\left(VP\right)\)

\(\Rightarrowđpcm\)

k(k+1)(k+2) -(k-1)k(k+1)

=k(k+1)(k + 2 - k + 1)

= 3k(k+1)  đpcm

 

Hayato
Xem chi tiết
Hà Lê Tuân Minh
31 tháng 1 2020 lúc 20:20

   k . (k+ 1) . (k+2) - k .(k +1) . (k-1)

=  [ (k+2)-(k -1) ] .k .(k+1)

= (k + 2 -k +1) . k .(k+1)

= 3k (k+1)

Vậy: k . (k+ 1) . (k+2) - k .(k +1) . (k-1) = 3k (k+1)

S = 1.2+2.3+...+n.(n+1)

3S = 3.1.2 +3.2.3+...+3.n. (n+1)

3S = 1.2.3 - 0.1.2 +2.3.4 -1.2.3 + ... + n . (n+1 ) . (n+2) - (n-1).n.(n+1)

3S = n.(n+1).(n+2)

Khách vãng lai đã xóa
Trịnh hà hoa
Xem chi tiết
Nguyễn Bảo Châu
Xem chi tiết
♥
Xem chi tiết
Trần Mạnh Nguyên
Xem chi tiết
đỗ thùy trang
Xem chi tiết